FEATURES OF THE LANGUAGE OF SOCIAL NETWORKS FACEBOOK, ON THE EXAMPLE OF TIK-TOK (American Journal of Research in Humanities and Social Sciences, 2024)
This article delves into the linguistic features of two prominent social networking platforms, Facebook and TikTok, shedding light on how users communicate and express themselves in these digital spaces. Employing a comprehensive approach encompassing annotation, literature analysis, methods, results, and discussion, this study aims to unravel the distinct characteristics that define the language of these platforms. By exploring these nuances, we can gain insights into the evolving landscape of social media discourse and its impact on digital communication.